CHARMed PyMca, Part I: A Protocol for Improved Inter‐laboratory Reproducibility in the Quantitative ED‐XRF Analysis of Copper Alloys. (24th February 2017) - Heginbotham, A.; Solé, V. A.
Abstract : This paper describes a protocol for quantification of heritage copper alloys by energy‐dispersive X‐ray fluorescence spectroscopy (ED‐XRF). The protocol, nicknamed CHARMed PyMca, is designed for users who wish to maximize inter‐laboratory reproducibility of quantitative ED‐XRF results for the wide range of copper alloys found in heritage materials. By maximizing reproducibility, this protocol should facilitate collaboration and allow the rigorous use of shared data and databases. The protocol uses free, open‐source, fundamental parameters software called PyMca. PyMca allows for a consistent and transparent application of the fundamental parameters approach independent of the ED‐XRF instrumentation used. The proposed protocol calls for calibration of standardless PyMca results against a set of certified reference materials designed specifically for use with heritage copper alloys, the so‐called copper CHARM set. Finally, this protocol calls for the calibration‐to‐standards to be carried out following a consistent strategy, including error modelling and the incorporation of a validation procedure. A reproducibility study was conducted using CHARMed PyMca and eight different ED‐XRF instruments of six different types. In comparison to a 2010 study conducted according to the same method, CHARMed PyMca showed a dramatic improvement in reproducibility and method sensitivity.